2019
DOI: 10.1074/jbc.tm117.000832
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism in pluripotency: Both driver and passenger?

Abstract: Downloaded from2 Pluripotent stem cells (PSCs) are highly proliferative cells characterized by robust metabolic demands to power rapid division. For many years considered a passive component or "passenger" of cell fate determination, cell metabolism is now starting to take center stage as a driver of cell fate outcomes. This review provides an update and analysis of our current understanding of PSC metabolism and its role in self-renewal, differentiation, and somatic cell reprogramming to pluripotency. Moreove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(48 citation statements)
references
References 100 publications
4
40
0
Order By: Relevance
“…In line with this observation, using genome-wide immunoprecipitation-based techniques, BMAL1 has been shown to target genes related to cellular metabolism in somatic cells (Hatanaka et al, 2010;Wu et al, 2017;Reinke & Asher, 2019), therefore pointing to a potential direct regulation of metabolic genes by BMAL1 through chromatin binding. Although until recently changes in metabolism were thought to be a consequence of differentiation, it is now clear that metabolism plays an active role in cell fate commitment, mainly by modifying the epigenome, which can in turn regulate pluripotency, differentiation, and somatic cell reprogramming (Dahan et al, 2019). Pluripotent stem cells favour glycolysis over OXPHOS, thus both reducing potential DNA damage by ROS, whereas increasing the amount of available intermediate metabolites for biosynthesis of lipids and nucleotides.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In line with this observation, using genome-wide immunoprecipitation-based techniques, BMAL1 has been shown to target genes related to cellular metabolism in somatic cells (Hatanaka et al, 2010;Wu et al, 2017;Reinke & Asher, 2019), therefore pointing to a potential direct regulation of metabolic genes by BMAL1 through chromatin binding. Although until recently changes in metabolism were thought to be a consequence of differentiation, it is now clear that metabolism plays an active role in cell fate commitment, mainly by modifying the epigenome, which can in turn regulate pluripotency, differentiation, and somatic cell reprogramming (Dahan et al, 2019). Pluripotent stem cells favour glycolysis over OXPHOS, thus both reducing potential DNA damage by ROS, whereas increasing the amount of available intermediate metabolites for biosynthesis of lipids and nucleotides.…”
Section: Discussionmentioning
confidence: 99%
“…Collectively, our results show that BMAL1 contributes to the proper transcriptional landscape regulation of pluripotent cells and that its depletion leads to the deregulation of metabolism-related transcriptional pathways. Changes in metabolic activity are closely linked to the exit of pluripotency, partly by influencing the epigenome during cell commitment (Cliff & Dalton, 2017;Dahan et al, 2019). Thus, we speculated that Bmal1 depletion can alter early cell differentiation potential through changes in the expression of metabolic gene networks that govern the balance between glycolytic and oxidative phosphorylation (OXPHOS) activity.…”
Section: Bmal1 Supports Glycolytic Metabolism In Escsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is to be noted that the TGFβ pathway is important for pluripotency due to its direct modulation of expression of Nanog (Xu et al, 2008). The increased expression of genes related to the glycolytic pathway in ARPE-19 cells, upon SPIR treatment, reflects the pluripotent state of these cells under these conditions, since aerobic glycolysis supports the maintenance of the pluripotent state by maintaining histone acetylation and the associated open chromatin structure of PSCs (Moussaieff et al, 2015;Gu et al, 2016;Folmes et al, 2011;Guda et al, 2018;Cliff et al, 2017, Dahan et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, the roles of cellular lipids and AlbuMAX in hPSCs have been well described. Some studies have demonstrated that AlbuMAX and cellular lipids, such as prostaglandin E2, linoleic acid, and fatty acid synthesis are essential for stem cell pluripotency (Garcia-Gonzalo and Izpisua Belmonte, 2008; Kim et al, 2009;Wang et al, 2017;Dahan et al, 2019). Moreover, a recent report has suggested that lipid deprivation in E8 based-cell culture media could promote a naïve-to-primed intermediate state via changes in the epigenetic landscape, naïve protein expression levels, and mitochondrial morphology (Cornacchia et al, 2019).…”
Section: Discussionmentioning
confidence: 99%